Incidental Diagnosis of a Primary Pure "Mixed" Ovarian Carcinoid: Clinicopathological Report and Concise Review of the Recent Series - Demetrio Larraín; María José Gárate; Lidia Díaz; Iván Rojas (Hindawi Limited, 2024)
Primary ovarian carcinoid tumors (POCT) are well-differentiated neuroendocrine neoplasms and account for <0.1% of ovarian tumors. POCT usually arise in the context of mature cystic teratoma; however, pure primary ovarian carcinoids without teratomatous or mucinous elements are very rare. We present a case of a 54-year-old woman that underwent total laparoscopic hysterectomy and bilateral salpingo-oophorectomy because of endometrial hyperplasia without atypia. The ovaries were macroscopically normal. Pathology report revealed a primary ovarian carcinoid with mixed trabecular and insular growth patterns. Immunohistochemical was positive for chromogranine A, synaptophysin, and CDX2. The Ki-67 index was <1%. To exclude a metastatic carcinoid to the ovary, a Ga-68 PET/CT was performed. This case highlights the microscopic and immunohistochemical characteristics of pure POCT and potential pitfalls in their differentiation from metastatic carcinoids. In addition, differential characteristics of primary and metastatic ovarian carcinoids are discussed.